2019
DOI: 10.1002/slct.201904020
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Polycarbonate/Polystyrene Bead Alloy via Solvent Evaporation Method

Abstract: In this study, a facile method to recycle wasted expandable polystyrene (PS) into polycarbonate (PC)/PS bead alloys is described in this paper, and compared with melt extrusion method. Results showed that the initial decomposition temperature of composite with 30 wt% PC increases by 25 °C and simultaneously enhances by 37.6% in tensile property compared to the neat PS via solvent evaporation method, however, a substantial drop in molecular weight with melt extrusion method. The solvent evaporation method provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Many studies regarding functional PS composites have been reported (Yan et al, 2011a;Yan et al, 2011b;Zheng et al, 2013;Umar et al, 2014;He et al, 2015;Wang et al, 2018;An et al, 2019;Li et al, 2019;Shi et al, 2021;Wang et al, 2022a;Wang et al, 2022b); moreover, PS/Fe 3 O 4 nanomaterials and micrometer size composites have been synthesized in the above studies; however, there is no report regarding the colorized and magnetic PS/Fe 3 O 4 beads with millimeter size. To the best of our knowledge regarding functional PS, many colorful extruding polystyrenes (XPS) are achieved by blending the PS with organic or inorganic pigments.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies regarding functional PS composites have been reported (Yan et al, 2011a;Yan et al, 2011b;Zheng et al, 2013;Umar et al, 2014;He et al, 2015;Wang et al, 2018;An et al, 2019;Li et al, 2019;Shi et al, 2021;Wang et al, 2022a;Wang et al, 2022b); moreover, PS/Fe 3 O 4 nanomaterials and micrometer size composites have been synthesized in the above studies; however, there is no report regarding the colorized and magnetic PS/Fe 3 O 4 beads with millimeter size. To the best of our knowledge regarding functional PS, many colorful extruding polystyrenes (XPS) are achieved by blending the PS with organic or inorganic pigments.…”
Section: Introductionmentioning
confidence: 99%